Wnt8B, transcriptionally regulated by ZNF191, promotes cell proliferation of hepatocellular carcinoma via Wnt signaling. Issue 2 (4th December 2020) - Liu, Yufeng; Wu, Di; Cheng, Hanghang; Chen, Lei; Zhang, Weidi; Zou, Liping; Gao, Qiongmei; Zhao, Zhonghua; Chen, Qi; Zeng, Wenjiao; Zhang, Zhigang; Jiang, Wei; et al.
Abstract: Dysregulation of wingless‐type (Wnt) signaling is implicated in hepatocellular carcinoma (HCC). Wnt family member 8B (Wnt8B), one of the canonical Wnt ligands, is implicated in oncogenesis. However, the role of Wnt8B in human HCCs and its transcriptional regulation mechanism are presently unknown . Here, we report that Wnt8B expression was frequently increased in HCCs and was significantly associated with poorer patient prognosis. Wnt8B knockdown suppresses HCC cell growth both in vitro and in vivo via inhibiting the canonical Wnt signaling. Zinc finger transcription factor 191 (ZNF191) can positively regulate Wnt8B mRNA and protein expression, and promoter luciferase assay indicated that ZNF191 can increase the transcription activity of the 2‐Kbps WNT8B promoter. Chromatin immunoprecipitation‐qPCR and electrophoretic mobility shift assay showed that ZNF191 protein directly binds to the WNT8B promoter, and the binding sites are at nt‐1491(ATTAATT) and nt‐1178(ATTCATT). Moreover, Wnt8B contributes to the effect of ZNF191 on cell proliferation, and Wnt8B expression correlates positively with ZNF191 in human HCCs. Our findings suggested that Wnt8B, directly transcriptionally regulated by ZNF191, plays a pivotal role in HCC proliferation via the canonical Wnt pathway and may serve as a new prognostic biomarker and a potential therapeutic target for HCC patients. Abstract : Aberrant activation of the canonical wingless‐type (Wnt) signaling is involved in hepatocellular carcinoma (HCC). Here, we report Wnt8B, one of the canonical Wnt ligands, is upregulated in human HCCs and is significantly associated with poorer prognosis. Zinc finger transcription factor 191 (ZNF191) can directly bind to the WNT8B promoter and transactivate the WNT8B gene and subsequently activate the Wnt pathway to promote cell proliferation. Wnt8B expression correlates positively with ZNF191 in HCC specimens. Thus, Wnt8B may serve as a new prognostic biomarker and a potential therapeutic target for HCC patients.